Self-adjoint Fuzzy Operator in Fuzzy Hilbert Space and its Properties - Rasheed, Sudad M. (Sulaimani Journal for Pure and Applied Sciences, 2017)
In this work, we focus our study on adjoint Fuzzy linear operator and self-adjoint Fuzzy linear operator acting on a Fuzzy Hilbert space (FH-Space). We have given several definitions, theorems and discuss in details, The properties of the adjoint and self-adjoint Fuzzy operators in a FH-adjoint Fuzzy operators in a FH-space.
Keywords: adjoint Fuzzy operators; selfadjoint Fuzzy operator; FHspace; FIPspace